2010
DOI: 10.1007/s13233-010-0313-7
|View full text |Cite
|
Sign up to set email alerts
|

Self-organization of amphiphilic diblock rod-coil molecule into supramolecular honeycomb and cylindrical aggregates and its application as Suzuki coupling reaction

Abstract: An aromatic amphiphilic molecule consisting of three biphenyl groups and one styrene unit linked together with ether bonds as a rigid rod segment, and poly(ethylene oxide) with 17 repeating units as a coil segment was synthesized and its self-assembly behavior in the bulk state and aqueous solution was examined by DSC, X-ray scattering, DLS and TEM. This molecule based on a rod building block self-assembles into lamellar or hexagonal perforated layer (HPL) structures in the crystalline phase or liquid crystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The supramolecular nanostructures of rod–coil molecules can be precisely tuned by the cooperative effects of several molecular parameters such as the ratio of rod to coil segments, rod anisotropy and coil cross‐sectional area 17–23. Lee's group and others have reported that rod–coil block systems are able to self‐assemble into one‐dimensional lamellae, two‐dimensional columnar structures, discrete bundles, ribbons, vesicles, and so on, depending on the relative volume fraction of rod segments 24–29…”
Section: Introductionmentioning
confidence: 99%
“…The supramolecular nanostructures of rod–coil molecules can be precisely tuned by the cooperative effects of several molecular parameters such as the ratio of rod to coil segments, rod anisotropy and coil cross‐sectional area 17–23. Lee's group and others have reported that rod–coil block systems are able to self‐assemble into one‐dimensional lamellae, two‐dimensional columnar structures, discrete bundles, ribbons, vesicles, and so on, depending on the relative volume fraction of rod segments 24–29…”
Section: Introductionmentioning
confidence: 99%
“…On further slow cooling to room temperature, a transition to a spherulitic texture with arced striations which are characteristic of a hexagonal perforated lamellar mesophase can be observed [Fig. 3(b)] 28. To confirm the self‐assembling structure of molecule 5 in the bulk state, X‐ray scattering experiments were performed at various temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…4(b)]. These reflections can be indexed as the, (100), (002), (110), (103), (004), and (006) planes for a 3‐D hexagonal structure (P6¯m2 space group symmetry) with lattice parameters a = 9.0 nm and c = 14.5 nm with c/a = 1.61 (see Supporting Information Table S1) 26, 28. It should be pointed out that the peak intensity associated with the (002) reflection displays the highest intensity, indicating that the supramolecular 3‐D layer structure is composed of an ABAB arrangement crystalline layer of the rod segments with in‐plane hexagonal packing of coil perforations [See Fig.…”
Section: Resultsmentioning
confidence: 99%
“…one‐dimensional (1‐D) lamellar, two‐dimensional (2‐D) columnar and three‐dimensional (3‐D) bundles. This is achieved by modifying non‐covalent driving parameters such as hydrophobic and hydrophilic effects, electrostatic interactions, hydrogen bonding, molecular shapes, cross‐sectional areas and microphase segregation . Lee and co‐workers have shown that rod–coil molecules incorporating lateral methyl groups in the middle of the rod segments spontaneously organise into hexagonal nanostructures in the liquid crystalline phase .…”
Section: Introductionmentioning
confidence: 99%